Information technologies as organizational support for the COVID-19 coping actions: Nurses' discourse - Haline Costa dos Santos Guedes; José Nildo de Barros Silva Júnior; Dilyane Cabral Januário; Débora Raquel Soares Guedes Trigueiro; Oriana Deyze Correia Paiva Leadebal; Anne Jaquelyne Roque Barrêto (Universidade de São Paulo, 2023)
Abstract Objective: to analyze nurses' discourse about the potentialities in using information technologies as organizational support for the COVID-19 coping actions in Primary Health Care. Method: a qualitative and exploratory study conducted in the Family Health Strategy units from the city of João Pessoa, Paraíba, Brazil. Data collection was carried out from September to November 2021 with 26 nurses selected through the snowball technique, resorting to a semi-structured interview script. The empirical material was organized in the Atlas.ti 9 software and grounded on the theoretical-methodological contribution of Discourse Analysis, French Line. Results: three discursive blocks were evidenced: innovation based on social media; health education actions; resoluteness in organizational actions, presenting the relevance of the WhatsApp®, Instagram® and Facebook® apps as strategic resources, in order to collaborate in the Primary Health Care are with the organization of health actions against COVID-19 by nurses. Conclusion: health units have the potential to strengthen the assistance provided through digital organizational devices; however, they need political support that invests in the structure and strategies to enhance organization of the health actions.